2006
DOI: 10.1055/s-2006-944716
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for early gastric cancer: results and degrees of technical difficulty as well as success

Abstract: The difficulty of ESD depends on the location and size of the lesion, as well as on the presence of ulceration. We would recommend that trainees should begin by carrying out ESD on lesions with a diameter of less than 20 mm without ulceration that are located in the lower third of the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
223
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(251 citation statements)
references
References 11 publications
13
223
2
2
Order By: Relevance
“…According to a recent meta-analysis, although ESD had higher en bloc and curative resection rates than endoscopic mucosal resection (EMR), operation time was longer, with higher risks of complications compared to EMR [7] . Previous reports showed that large tumor size, location of the lesion in an upper region of the stomach, and long procedure time are risk factors for perforation following ESD [8][9][10][11][12][13] . Although perforation may be the most serious complication in the ESD procedure, most studies have reported recovery from perforation with conservative management such as endoscopic clipping, fasting, nasogastric aspiration, and broad-spectrum antibiotics [1,14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent meta-analysis, although ESD had higher en bloc and curative resection rates than endoscopic mucosal resection (EMR), operation time was longer, with higher risks of complications compared to EMR [7] . Previous reports showed that large tumor size, location of the lesion in an upper region of the stomach, and long procedure time are risk factors for perforation following ESD [8][9][10][11][12][13] . Although perforation may be the most serious complication in the ESD procedure, most studies have reported recovery from perforation with conservative management such as endoscopic clipping, fasting, nasogastric aspiration, and broad-spectrum antibiotics [1,14] .…”
Section: Introductionmentioning
confidence: 99%
“…Although perforation may be the most serious complication in the ESD procedure, most studies have reported recovery from perforation with conservative management such as endoscopic clipping, fasting, nasogastric aspiration, and broad-spectrum antibiotics [1,14] . However, the previous reports regarding clinical outcomes of perforation during ESD are retrospective analyses [5,8,9,[13][14][15] . More recently, prospective studies by Onogi et al [16] and our group [17] found that "transmural air leak" or "silent" free air without endoscopically visible perforation detected only by computed tomography (CT) did not affect the post-ESD clinical course.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic submucosal dissection (ESD) is an established treatment method in Japan that does not rely on snare techniques for the dissection of submucosal tissue and allows en-bloc resection of even large EGCs [2][3][4][5][6]. Moreover, submucosal tissue can be resected with sufficient vertical distance from the muscularis mucosae.…”
Section: Introductionmentioning
confidence: 99%
“…23 This is much lower than with ESD (1-6%). [24][25][26] Moreover, it is noteworthy that there was no significant difference regarding the recurrence rate in the APC groups, on an outpatient and admission basis. In addition, no complication was observed in both groups.…”
Section: 21mentioning
confidence: 86%